New social bandits? A comparative analysis of gangsterism in the Western and Eastern Cape provinces of South Africa - Petrus, Theodore (Criminology & criminal justice, 2019)
Gang violence has been extensively highlighted as an issue of national concern in South Africa. Gangs also pose concerns about the social contexts of the communities in which they are found. The Western Cape and Eastern Cape provinces have had the most prolific occurrences of gangsterism. Here gangs have demonstrated unique characteristics that set them apart from gangs in other areas. This article examines the context of gangsterism in the selected provinces by means of a comparative analysis. The purpose is to provide some strategies for effective intervention. The discussion also interrogates how or why intervention efforts may have failed and what could be improved in order to strengthen the chances of success of future interventions in affected communities.